Television Drama, Narrative Engagement and Audience Buying Behavior : The Effects ofWinter Sonatain Japan - Do Kyun Kim and Do Kyun Kim, and Singhal, Arvind and Hanaki, Toru and Dunn, Jennifer and Chitnis, Ketan and Min Wha Han, (International Communication Gazette, 2009)
In the past few years, the popularity of Korean television dramas, songs and movies has skyrocketed in countries of North and Southeast Asia. This huge wave of Korean pop culture is referred to as the Hanryu (the Korean wave). One of the most significant trendsetters of the Hanryu was the Korean television drama Winter Sonata, which was remarkably popular in every Asian country where it was broadcast. The present article investigates the perception of Japanese audience members toward Winter Sonata’s narrative and how this perception influenced their buying behavior of Winter Sonata memorabilia, such as clothing, cosmetics, DVDs/CDs of the program, trips to Korea and the like. Employing both qualitative and quantitative methods, this study finds that the popularity of the drama was generated by Japanese audiences’ engagement with its narrative. Further, the audience perception of the narrative’s quality was found to predict whether or not they purchased a Winter Sonata product.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNzQ4MDQ4NTA5MzQxODk0